2023
DOI: 10.1055/s-0043-1770901
|View full text |Cite
|
Sign up to set email alerts
|

The State-of-the-Art of Patient Portals: Adapting to External Factors, Addressing Barriers, and Innovating

Tera L. Reynolds,
Jared Guthrie Cobb,
Bryan D. Steitz
et al.

Abstract: Background and Objective Recent external factors—the 21st Century Cures Act and the coronavirus disease 2019 (COVID-19) pandemic—have stimulated major changes in the patient portal landscape. The objective of this state-of-the-art review is to describe recent developments in the patient portal literature and to identify recommendations and future directions for the design, implementation, and evaluation of portals. Methods To focus this review on salient contemporary issues, we elected to center it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 150 publications
0
1
0
Order By: Relevance
“…5 Beyond making the process of granting or receiving shared access easier, health systems, electronic health record vendors, patients and care partners should all engage together in conversations about how patient privacy is affected by shared access, as each have a significant role to play in protecting privacy while also improving access. [20][21][22] Protecting patient data from unauthorized disclosure is a central goal of the Health Insurance Portability and Accountability Act (HIPAA). Administrative processes that were noted as difficult (e.g., paper forms, requiring in person registration) were likely put in place by organizations to comply with HIPAA and ensure that only people specifically authorized by the patient were granted access to their health information.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 Beyond making the process of granting or receiving shared access easier, health systems, electronic health record vendors, patients and care partners should all engage together in conversations about how patient privacy is affected by shared access, as each have a significant role to play in protecting privacy while also improving access. [20][21][22] Protecting patient data from unauthorized disclosure is a central goal of the Health Insurance Portability and Accountability Act (HIPAA). Administrative processes that were noted as difficult (e.g., paper forms, requiring in person registration) were likely put in place by organizations to comply with HIPAA and ensure that only people specifically authorized by the patient were granted access to their health information.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Develop and evaluate the ecosystem around patient portals. A recent review of patient portal research identified important areas of focus, including understanding the consequences of increased patient access, evaluating new virtual care practices, understanding barriers to proxy use, and addressing disparities in portal adoption and use . Patient portals have tremendous potential to empower patients and families through carefully designed innovation, policymaking to encourage adoption, and ubiquitous access and use.…”
mentioning
confidence: 99%